Benefits of managerial overconfidence for corporate digital transformation: Evidence from China. - Yi Jin; Chuxin Chen; Bo Liu (PLoS ONE)
This article studies how managerial overconfidence shapes a firm's digital transformation and unpacks the pathway and the boundary condition. Using a sample of Chinese listed firms between 2011 and 2022, we find that managerial overconfidence exhibits a positive relationship with corporate digital transformation and the relationship is mediated by R&D investment. In addition, we demonstrate that compared to state-owned companies, R&D investment has a more significant positive effect on digital transformation in non-state-owned companies. This study contributes novel insights about the consequences of cognitive biases of top managers and extends the studies for investigating top managers in the digital transformation age. The findings offer implications for top managers who have to fully recognize the impact of overconfidence on the development of the companies and the impact of overconfident executives on corporate digital transformation depending on R&D investment to create value. In addition, this study also reminds Chinese policymakers to improve the efficiency of converting R&D investment into digital transformation in state-owned enterprises.